Regional Innovation: Government policies and the role of Higher Education Institutions - Dubarle, Patrick; Woyessa, Yali (UJ Press, 2016)
"This book provides an excellent analysis of regional innovation policy issues and developments with a wealth of examples, notably from OECD countries. Key policy areas, such as clusters, support services, and higher education institutions, are well documented. The research methodology is founded on the experience accumulated by the authors over several decades in many different countries in the context of a world class international organisation. This allows a good selection of policy relevant examples and an experienced presentation of them." - Jean-Eric Aubert, Former programme manager, World Bank and OECD